Sosialisasi Strategi Pemasaran Hasil Tani Desa Simpursia - Faisal; Nurman Dai Basri; Dandy Saputra; Adelia Putri Pratiwi (Compile Journal of Society Service, 2024)
The welfare of farmers in Simpursia Village, Pammana District, Wajo Regency remains a critical issue, particularly in terms of agricultural product marketing. The traditional marketing system, which involves many intermediaries, results in low profits for farmers. This Socialization activity aims to enhance farmers' understanding of efficient marketing strategies through socialization, including the identification of superior products and the use of digital technology. This approach is expected to help farmers market their products directly to end consumers, increasing income and reducing dependency on intermediaries. The evaluation of this activity, using the CIPP model (Context, Input, Process, Product), showed an increase in farmers' knowledge and active participation in the socialization activities. The conclusion of this initiative indicates its success and highlights the need for further training on digital platform marketing to ensure the sustainability of agricultural businesses.